An Eriksonian Reading of The Body by Hanif Kureishi: Integrity Versus Despair - Güngör, Pınar Süt (My University, 2023)
The ageing body and old age issues are among the prominent concerns of Western civilization throughout 21st century. The body, as the new raw material of consumer society, is perceived as something that can be changed as a result of medical developments and even bought and sold like other commodities. Furthering the cause of this transformations Erik Erikson’s psychosocial theory which evokes the quintessence of social pressure on elder people may help to receive the complexity of the issue. In his theory, Erikson posits eight stages of development with specific tasks and crisis peculiar to each stage throughout the life span. This paper represents an attempt to examine Hanif Kureishi’s The Body novella within the framework of Eriksonian psychosocial theory of human development. Admittedly, Kureishi’s short fiction appears to be in the main dealt with ethnicity and identity matters that render the postcolonial approach. Yet, this study is significant in that it deals with the pressures of society, becoming increasingly severe against old people, on ageing, which points out the last stage of Erikson, integrity vs. despair. It also reveals that past experiences and personal desires affect someone’s psyche. Through The Body, the tie between society and individual, desires and realities, appearance and internal existence have been affirmed. It may be concluded when Hanif Kureishi’s The Body is evaluated within the framework of Erikson’s psychosocial development theory, the accuracy of the effects of socio-cultural factors on personality development has been determined.